Propagation and Production of False Rosemary - Mack Thetford; Debbie Miller (EDIS)
False rosemary (Conradina canescens Gray [Lamiaceae]) is common to coastal areas of west Florida and is known to contribute to beach mouse habitat. This species can be considered a drought-tolerant landscape plant. Coastal homeowners interested in diminished water and fertilizer application may consider the use of false rosemary in landscapes of coastal developments. This document is Fact Sheet ENH 973, from the Environmental Horticulture Department and the Wildlife Ecology and Conservation Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: March 25, 2004.